(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this work, bis-carbamates of the MEE series were studied for the effectiveness of inhibitory properties for metal structures of oil refineries. The gravimetric method was used for the study. The best inhibitory properties of bis-carbamates of the MEE series have been revealed. The effectiveness of corrosion protection exceeded control. In this connection, it is possible to propose the use of these substances as metal corrosion inhibitors.